2019
DOI: 10.3389/fpsyt.2019.00567
|View full text |Cite
|
Sign up to set email alerts
|

A 1.5-Year Longitudinal Study of Social Activity in Patients With Schizophrenia

Abstract: Patients with schizophrenia exhibit impairments in their social activity, intelligence quotient (IQ), daily living skills, and social function. Social activity is a high-order outcome measure of their lives. Here we attempted to longitudinally evaluate the effects of IQ, daily living skills, social function, psychiatric symptoms, and medications on social activity in patients with schizophrenia. The purpose of the current study is to identify the specific factor that affects longitudinal changes in social acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…The duration of illness may also affect the results. A 1.5-year longitudinal study found that cognitive function, daily living skills, social function, and social activity were nominally improved over a 1.5-year follow-up period in SZ patients (28). The patients involved in the present study had an average illness duration of more than 24 months, and they all had cognitive impairment.…”
Section: Vft Performance and Tol Performancementioning
confidence: 55%
“…The duration of illness may also affect the results. A 1.5-year longitudinal study found that cognitive function, daily living skills, social function, and social activity were nominally improved over a 1.5-year follow-up period in SZ patients (28). The patients involved in the present study had an average illness duration of more than 24 months, and they all had cognitive impairment.…”
Section: Vft Performance and Tol Performancementioning
confidence: 55%
“…21 IQ discrepancy was estimated by subtracting premorbid IQ from current EIQ. 22 A variable for work outcome Total work hours per week were obtained from the Social Activity Assessment (SAA) 23 and used as a measure of work outcome. The SAA is a simplified version of the Modified Social Adjustment Scale-Work Outcome (details available from the author on request).…”
Section: Variables For Intelligencementioning
confidence: 99%
“…Studies on neurocognition have been performed to identify diseaseassociated changes in the cognitive and social functions of psychiatric patients using the database of neurocognitive batteries (Fujino et al, 2014(Fujino et al, , 2016Ohi et al, 2019;. A representative achievement is related to the works on cognitive decline of patients with schizophrenia.…”
Section: Neurocognitionmentioning
confidence: 99%